The Authorship in the Production of Open Educational Resources in the Multinational Context - Knihs, Everton (2017)
The concept of authorship related to the new technologies of information and communication, especially when created collaboratively, draws a discussion that presents different legal interpretations in the relations between different nations. The production of open educational resources is not a multinational context involving authors who bring with them the legal framework they are subject to. Discussing the legal elements involved with authors of a work produced in digital pallet becomes necessary for a definition of the future of the work. The resource produced in a collaborative way presents challenges not understood and adoption of a single legal proposal there are no clear legal milestones for authorship of multinational collaborative works. Copyright is suitable for this new production of collaborative works. This article presents the legal elements and how they influence the production of open educational resources, especially in the production of open text textbooks, and their production should be observed and discussed previously, in order to avoid future legal demands and evolve the legal concepts involved between different nations.